TG13 surgical management of acute cholecystitis - Yamashita, Yuichi; Büchler, Markus W. (Journal of hepato-biliary pancreatic sciences, 2013)
Background Laparoscopic cholecystectomy is now accepted as a surgical procedure for acute cholecystitis when it is performed by an expert surgeon. There are several lines of strong evidence, such as randomized controlled trials (RCTs) and meta-analyses, supporting the introduction of laparoscopic cholecystectomy for patients with acute cholecystitis. The updated Tokyo Guidelines 2013 (TG13) describe the surgical treatment for acute cholecystitis according to the grade of severity, the timing, and the procedure used for cholecystitis in a question-and-answer format using the evidence concerning surgical management of acute cholecystitis. Methods and materials Forty-eight publications were selected for a careful examination of their full texts, and the types of surgical management of acute cholecystitis were investigated using this evidence. The items concerning the surgical management of acute cholecystitis were the optimal surgical treatment for acute cholecystitis according to the grade of severity, optimal timing for the cholecystectomy, surgical procedure used for cholecystectomy, optimal timing of the conversion of cholecystectomy from laparoscopic to open surgery, and the complications of laparoscopic cholecystectomy. Results There were eight RCTs and four meta-analyses concerning the optimal timing of the cholecystectomy. Consequently, it was found that cholecystectomy is preferable early after admission. There were three RCTs and two meta-analyses concerning the surgical procedure, which concluded that laparoscopic cholecystectomy is preferable to open procedures. Literature concerning the surgical treatment according to the grade of severity could not be quoted, because there have been no publications on this topic. Therefore, the treatment was determined based on the general opinions of professionals. Conclusion Surgical management of acute cholecystitis in the updated TG13 is fundamentally the same as in the Tokyo Guidelines 2007 (TG07), and the concept of a critical view of safety and the existence of extreme vasculobiliary injury are added in the text to call the surgeon's attention to the need to reduce the incidence of bile duct injury.
Gesehen am 23.07.2021